AN INTUITIVE ANDROID-BASED SOFTWARE DESIGN FOR POTENTIOSTAT-BASED URIC ACID TESTING PLATFORM - Fransiscus Munthe, Michael
Uric acid, as a potential biomarker that continues to be developed, requires an advanced instrument to carry out readings and assist analysis. The instrument is a portable testing platform that has been designed on the basis of a potentiostat. However, under current conditions, the existing test platform has never been tested on a biosensor with the target analyte in the form of uric acid, so electrochemical analysis and concentration measurement cannot be carried out. Then other needs arise regarding the future development of wearable technology, so that the initiation of this development starts on a portable platform. But in fact, the platform that has been created as hardware cannot run alone, which requires another component, namely software to display the results of the measurement process and as user control to use the application. So this article is here to focus on developing a portable testing platform from the software side. The software used is made using MIT App Inventor, which is an integrated application development environment. Then this software is formed by having two main subsystems as its architecture, namely the device management system subsystem, which acts as the back-end, and the user interface subsystem, which acts as the front-end of the application. This device management system subsystem will directly relate to the hardware, where